Measurement and interpretation of fermion-pair production at LEP energies above the Z resonance - Abdallah, J; Abreu, P; Adam, W; Adzic, P; Albrecht, T; Alderweireld, T; Alemany-Fernandez, R; Allmendinger, T; Allport, P; Amaldi, U; Amapane, N; Amato, S; et al. (2006)
This paper presents DELPHI measurements and interpretations of cross-sections, forward-backward asymmetries, and angular distributions, for the e-e- → ff̄ process for centre-of-mass energies above the Z resonance, from √s ∼ 130-207 GeV at the LEP collider. The measurements are consistent with the predictions of the Standard Model and are used to study a variety of models including the S-Matrix ansatz for e -e- → ff̄ scattering and several models which include physics beyond the Standard Model: the exchange of Z′ bosons, contact interactions between fermions, the exchange of gravitons in large extra dimensions and the exchange of ṽ in R-parity violating supersymmetry.